Functional Capacity Evaluation for Injuries to the Foot and Ankle. (November 2019) - Idarraga, Alexander J.; Wright-Chisem, Adam; Bohl, Daniel D.; Lee, Simon; Lin, Johnny; Holmes, George B.; Hamid, Kamran S.
Background: The functional capacity evaluation (FCE) is used to determine physical ability after treatment of a workplace-related injury. This evaluation is a determinant in the administration of benefits and the decision to return to work (RTW). The purpose of this study was to characterize FCE results and ability to RTW after treatment for workplace-related orthopedic injuries to the foot or ankle. Methods: A retrospective medical record review from the practices of 4 orthopedic foot and ankle surgeons was conducted. Inclusion criteria were a workplace-related injury to the foot or ankle, at least 2 years of follow-up, and an associated FCE. The FCE report and clinic notes were used to determine the patient's preinjury job requirement, postinjury FCE-determined ability, specific FCE- or physician-imposed work restrictions, and clearance to RTW. A total of 188 patients met inclusion criteria. Results: In total, 74.4% of patients had FCE-determined work abilities at or above their preinjury job requirements, and 63.3% of patients were cleared to RTW. The mean time from injury to FCE was 1.9 ± 1.5 years, and the mean time to clearance for RTW was 2.0 ± 1.3 years. A less strenuous preinjury job requirement was positively associated with both the FCE-determined ability meeting the preinjury job requirement ( P < .001) and clearance to RTW ( P = .034). Conclusion: Two in 3 patients were cleared to RTW following workplace-related injuries to the foot or ankle culminating in an FCE. However, it took a mean of 2 years to achieve this clearance. Patients with more strenuous jobs were less likely to be able to RTW after injury. Level of Evidence: Level III, retrospective comparative study.